Virtual, augmented and mixed reality : interaction, navigation, visualization, embodiment, and simulation : 10th International Conference, VAMR 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: interaction, navigation, visualization, embodiment, and simulation : 10th International Conference, VAMR 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I (2018) - Unknown
No abstract available